A Bibliometric Review of Research on Venture Capital - Mohamed Cherif Benzouai; Khalid Djeffal (Asian Academy of Management Journal, 2021)
Venture capital is a cross-cutting discipline and research field. This study used bibliometric indicators of publications indexed in Web of Science (WOS) Core Collection over the last two decades to provide an overview of the main characteristics of its publications. A total of 1,840 papers by 2,607 authors in 518 journals were reviewed. The publications were examined in terms of temporal trend, geographical and institutional distribution, references, authors, and citations. The results indicate that the importance of venture capital research is increasing. In terms of impact, a small group of productive countries (e.g., USA and UK) and authors (e.g., Cumming and Wright) contributed to a signi?cant share of these publications. Whereas China is expected to attract more attention to this topic in the future. Harvard University is the most productive institution and the Journal of Business Venturing is the most active journal. By topic, publications that address the contribution of venture capital to entrepreneurship are the most cited. New areas of research have focused especially on the implication of signal theory in venture capital networks, support for decision-makers and crowdfunding as a new investment strategy. Today, the microlevel is the dominant level (compared to the macro-level) in venture capital research. The results of this study aim to contribute to supporting decision making in a venture capital research management context and to serve as a guide for future researchers or evaluators.